TRAINING ON MAKING INTERACTIVE LEARNING MEDIA USING POWERPOINT TO IMPROVE TEACHER COMPETENCE - Lorensius, Lorensius; Anggal, Nikolaus; Darung, Afrianus; Antonius, Zecres (LPPM Univ. Ibn Khaldun Bogor, 2023)
This article describes community service activities related to training on making interactive learning media using PowerPoint to improve teacher competence. This service activity uses training methods by creating learning media that contain basic competencies, core competencies, learning objectives, learning materials, and learning evaluation. The participants who participated in this training were Catholic religion teachers in elementary and junior high schools totaling 30 participants. The results of this service increase teacher competence in designing and utilizing PowerPoint-based interactive learning media to support the learning process. The results of the evaluation of activities show positively that participants gain new knowledge and can improve their competence. Participants also revealed the use of interactive media PowerPoint is easy to understand and can help users in operating learning media. The evaluation questionnaire also showed a positive response from participants, namely an average percentage of 81.4% with the category agree. Teachers can overcome the problem of using learning media through training activities and collaborating in competency improvement activities.